2007
DOI: 10.1111/j.1439-0396.2007.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nucleotides protect thymocyte DNA from damage induced by cyclophosphamide in mice

Abstract: The effects of dietary nucleotides on thymocyte DNA damages induced by cyclophosphamide (CP) in mice were examined. First, phase I experiment was conducted to determine the optimal timing of detecting thymocyte DNA damages induced by CP (150 mg/kg body weight) in mice. Thymocyte DNA damages was determined at 6, 12, 18, 24 h by single-cell gel electrophosphoresis assay (comet assay) after intraperitoneal injection of CP. The levels of DNA damage at 6, 12, 18, 24 h were all significantly higher than that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Previously, Frankič also reported that dietary nucleotides could reduce the amount of DNA damage induced by T-2 toxin in immune cells [ 3 ]. In addition, the dietary nucleotides could reduce cyclophosphamide-induced DNA damage in immune organs in mice [ 21 ]. Our results were consistent with these reports, since nucleotides exerted protective effects on DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Frankič also reported that dietary nucleotides could reduce the amount of DNA damage induced by T-2 toxin in immune cells [ 3 ]. In addition, the dietary nucleotides could reduce cyclophosphamide-induced DNA damage in immune organs in mice [ 21 ]. Our results were consistent with these reports, since nucleotides exerted protective effects on DNA.…”
Section: Discussionmentioning
confidence: 99%
“…They have important effects on the growth and development of rapid turnover cells, such as those in the -E-mail: paola.superchi@unipr.it immune system and in the gastrointestinal tract (Wang et al, 2008). In healthy conditions dietary nucleotides are probably not essential, however, during stressful or limited nutrient intake periods, dietary nucleotides may become essential (Dancey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As an important molecule for biological composition (Sánchez‐Pozo & Gil, 2002 ), nucleic acids have been reported to have a variety of beneficial physiological functions, such as antioxidation (Wang et al, 2008 ), improving immunity (Cheng et al, 2018 ; Xu et al, 2013 ), liver function (Kojima‐Yuasa et al, 2016 ; Sauer et al, 2012 ), and growth performance and nutrient utilization (Waititu et al, 2015 ), repairing intestinal injury (Meng et al, 2017 ) and regulating intestinal flora (Sauer et al, 2012 ). However, the use of natural macromolecular nucleic acids in medicine and food processing is limited because of their insolubility in water and low bioavailability.…”
Section: Introductionmentioning
confidence: 99%